Back Cover: Plasma Process. Polym. 2∕2014. Issue 2 (February 2014) - Intranuovo, Francesca; Gristina, Roberto; Brun, Francesco; Mohammadi, Sara; Ceccone, Giacomo; Sardella, Eloisa; Rossi, François; Tromba, Giuliana; Favia, Pietro
<x xml:space="preserve">Abstract</x> Back Cover: High porous PCL scaffolds chemically modified by means of low pressure plasma deposition processes, improved the adhesion of osteoblast cells along the edges and inside the square‐shaped pores (green stained fluorescence for actin cytoskeleton, blue for nuclei). SR Micro‐CT images together with skeleton analysis allowed a detailed morphological characterization. Further information can be found in the paper by Francesca Intranuovo et al. on page 184. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>